Komunikasi Interpersonal Konselor dalam Mengatasi Anxiety Problem Konseli: Kajian Konseling Islam - Salman; Angga Prayuda; Amin Sitorus, M.Darul; Sikumbang, Ahmad Tamrin (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research aims to find out how counselors' interpersonal communication works in resolving counselors' anxiety problems: Islamic counseling studies. The data mining technique in this research uses a qualitative approach using library research techniques, namely collecting data through several pieces of literature that are related to the discussion. The method used in this research is descriptive analysis. The findings obtained by the author in this research are that interpersonal communication in the counseling process is very necessary, especially during deep interviews with clients in order to overcome anxiety. Furthermore, the suggestion process is carried out in order to strengthen the counselee's mentality so that the counselee can solve the problem independently.